3D Interaction with Mouse-Keyboard, Gamepad and Leap Motion: A Comparative Study - Pittarello, Fabio; Dumitriu, Alexandru; Piazza, Elisa (Smart Objects and Technologies for Social Good, 2018)
Serious gaming can represent a key for fostering learning and letting children to acquire new information and skills while doing engaging activities. Among the different types of games, those ones based on interactive 3D environments are widely diffused and appreciated. A key component of the design of these experiences is the choice of the input device that will be used by the players and the mapping of the users’ intentions to the actions in the 3D environment. The choice of the proper device can lead to benefits in terms of user engagement, which often is the prerequisite for learning. There are also additional dimensions to consider, as the usability and the physical fatigue. Their undervaluation, in an educational context, can hamper the successful outcome of the experience. For this reason in this work we compared the use of three different input devices (a mouse-keyboard set, a gamepad and the Leap Motion, a sensor for recognizing hand gestures) for controlling a 3D educational gaming experience focused on environmental sustainability. We organized a comparative study with 30 children of the Primary School, evaluating the interaction in terms of usability, engagement and physical fatigue. The results evidenced the potential of the Leap for engaging the children, but also drawbacks in terms of usability and physical fatigue that should be taken into consideration for the development of this technology and the design of experiences based on it.